2010
DOI: 10.1002/da.20701
|View full text |Cite
|
Sign up to set email alerts
|

The acquired capability for suicide: A comparison of suicide attempters, suicide ideators, and non-suicidal controls

Abstract: Background The Interpersonal Theory of Suicide states that to make a serious or lethal suicide attempt a person must experience reductions in fear and pain sensitivity sufficient to overcome self preservation reflexes (i.e., the acquired capability for suicide). The purpose of the current study was to examine the fearlessness component of the acquired capability for suicide using self-report assessment instruments and an objective measure of aversion (the affectively modulated startle reflex task). Methods D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
135
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(151 citation statements)
references
References 23 publications
(29 reference statements)
12
135
3
1
Order By: Relevance
“…We also provide further support for research (Orbach, Mikulincer, & King et al, 1997;Smith et al, 2010) indicating that suicide attempters have higher fearlessness about injury and death than do non-suicidal controls, and suicide ideators.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We also provide further support for research (Orbach, Mikulincer, & King et al, 1997;Smith et al, 2010) indicating that suicide attempters have higher fearlessness about injury and death than do non-suicidal controls, and suicide ideators.…”
Section: Discussionsupporting
confidence: 73%
“…There is also emerging evidence that suicide capability is elevated among suicide attempters relative to suicide ideators (Smith, Cukrowicz, Poindexter, Hobson, & Cohen, 2010;Van Orden, Witte, Gordon, Bender, & Joiner, 2008), and that restricted physical access to lethal means may reduce the likelihood of suicide attempts (Baber & Miller, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Even though closely associated, different biological mechanisms may underlie these phenomena and may be linked to distinct patient populations and personality dimensions (Huang et al, 2000;Gil, 2005;Conrad et al, 2009;Smith et al, 2010). In comparison with previous research published by Gil (2005) Our results correspond to the data regarding lifetime prevalence of suicide attempts in chronic schizophrenic samples (Radomsky et al, 1999;Kasckow et al, 2011) …”
Section: Discussionsupporting
confidence: 82%
“…Taliaferro and Muehlenkamp (2014) found that hopelessness and depression were higher among adolescent ideators than non-suicidal adolescents, but comparable between ideators and attempters; conversely, a self-injury history (a volitional phase factor) was more likely among attempters than ideators. There is also evidence to suggest that suicide capability is elevated among suicide attempters relative to suicide ideators (Smith, Cukrowicz, 2010;Van Orden, 2008), and that restricted physical access to lethal means may reduce the likelihood of suicide attempts (Baber and Miller, 2014 Most students described their sexual orientation as heterosexual/straight (84.7%).…”
Section: Introductionmentioning
confidence: 99%